Design of Aqueous Two-Phase Protein Separation Systems - Ahmad, Murni M (2005)
Aqueous Two-Phase System (ATPS), despite its potential as a bulk protein separation technique that offers high yield, low cost and mild environment, has limited application at industrial scale. The work proposes an integrated framework that calculates flowsheet design for the application of ATPS to extract a target protein from cell lysate. The framework integrates the liquid-liquid equilibrium calculation based on Flory-Huggins Model and the mass balance calculation for the flowsheet. The applicability of the framework is demonstrated using a case study on a multi-stage extraction of phosphofructokinase and ovalbumin using PEG6000-DxT500 and PEG6000-Na3PO4 ATPSs.